The Right of State to Restrict Human Rights - Sadiković, Lada (Kriminalističke teme, 2004)
Democratic state can come into different critical situations wich always means essential reduce of it's possibility to protect human rights. Development of democracy coincides with spreading and increasing catalog of human rights, imposed the need to create certain mechanism wich, make possible certain restriction of human rights in crises situations, in order to protect the whole democratic order. However it sounds paradoxical, very clear restrictions under certain conditions as exeptions, special restrictions, derogations and reservations has to be treated as one aspect of whole protection of human rights wich are contained in Convention.